2003
DOI: 10.1046/j.1360-0443.2003.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Opiates, cocaine and alcohol combinations in accidental drug overdose deaths in New York City, 1990–98

Abstract: These data suggest that interventions to prevent accidental overdose mortality should address the use of drugs such as heroin, cocaine and alcohol in combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
199
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(218 citation statements)
references
References 30 publications
18
199
0
1
Order By: Relevance
“…Typically, as indicated by examination of patterns of use, individuals who initiate more than one substance progress from alcohol and/or tobacco as the first substance initiated to more "illicit" drugs, such as marijuana (Kandel and Yamaguchi, 2002). Further, research has consistently documented that a greater degree of substance involvement indicated by use of more than one substance leads to more problematic outcomes (Coffin et al, 2003;Degenhardt et al, 2007;Ives and Ghelani, 2006;McCabe et al, 2006;Schensul et al, 2005;Wish et al, 2006). For these reasons adolescents considered to be at higher risk were those who had initiated more than one substance.…”
Section: Pretest Equivalencementioning
confidence: 99%
See 1 more Smart Citation
“…Typically, as indicated by examination of patterns of use, individuals who initiate more than one substance progress from alcohol and/or tobacco as the first substance initiated to more "illicit" drugs, such as marijuana (Kandel and Yamaguchi, 2002). Further, research has consistently documented that a greater degree of substance involvement indicated by use of more than one substance leads to more problematic outcomes (Coffin et al, 2003;Degenhardt et al, 2007;Ives and Ghelani, 2006;McCabe et al, 2006;Schensul et al, 2005;Wish et al, 2006). For these reasons adolescents considered to be at higher risk were those who had initiated more than one substance.…”
Section: Pretest Equivalencementioning
confidence: 99%
“…Among the more serious types of substance use, poly-substance use (i.e., the use of different substances on the same or different occasions- Toumbourou and Catalano, 2005), is particularly important to consider. Adolescent poly-substance use is associated with a number of problematic outcomes, such as adverse psychological and social consequences, particularly for girls (Lex, 1995;Overman et al, 2004), increased delinquent acts for boys (Mason and Windle, 2002), an increased likelihood of developing substance abuse and other mental health problems in adulthood (Newcomb and Felix-Ortiz, 1992;Toumbourou and Catalano, 2005), lower levels of adolescent achievement motivation and adult job-related problems (Mohler-Kuo et al, 2003;Stein et al, 1993), accidental death due to drug overdose (Coffin et al, 2003), suicide (Midanik et al, 2007), high-risk sexual behaviors (Midanik et al, 2007), and substance-related accidents in adulthood .…”
Section: Introductionmentioning
confidence: 99%
“…The LACC data include several variables of interest: demographics, circumstances of death, time and location of death, and complete toxicology results. Coroner and medical examiner data have been used to examine various aspects of drug-related mortality in numerous other jurisdictions, including agencies from New Mexico, 21,22,32 New York City, [23][24][25] Georgia, 33 Maine, 34 Canada, 35 Sweden, 31 Australia, 36 and England. 37,38 The Centers for Disease Control and Prevention have also issued several reports on drug-related deaths using data from medical examiners in Multnomah County, Oregon; 39 King County, Washington; 40 Utah; 7 and New Rates are per 100,000 population and age adjusted to the 2000 US population a The different drug categories are not mutually exclusive; many deaths tested positive for drugs in more than one category Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Studies in New York City looked at deaths caused by certain substances such as heroin, methadone, opiates, cocaine, and alcohol and at differences in drug deaths by racial/ethnic groups. [23][24][25] These studies relied either on the coroner to identify which deaths were drug related or on a manual review of coroner cases to identify drug related deaths.…”
Section: Introductionmentioning
confidence: 99%
“…In the VIDUS cohort, cocaine injection has been identified as a predictor of both HIV and HCV prevalence (Patrick et al, 1997;Spittal et al, 2003). Reviews of overdose mortality among IDUs have identified (combination) drug use -specifically involving opioids and cocaine -as a major determinant of overdose fatality (O'Driscoll et al, 2001;Coffin et al, 2003;Darke & Hall, 2003). During the massive spike of fatal drug overdose incidents in British Columbia in the mid1990s, cocaine use had been present in a disproportionate number of overdose incidents .…”
Section: Risks and Harms Associated With Cocaine And Crack Usementioning
confidence: 99%